A comparative study on the antioxidant and immunomodulatory properties of curcumin conjugated gold nanospheres and free curcumin - Leichombam Mohindro Singh, Biswajit Chakraborty, Ramkrishna Pal, Anupam Nath, Sudip Pal, Dewan Shahidur Rahman, Sujit Kumar Ghosh, Mahuya Sengupta (Journal of Applied Pharmaceutical Science, 2017)
Curcumin, a phenolic compound isolated from the rhizomes of the plant Curcuma longa, has been known for decades. Owing to the fact of its hydrophobic nature and rapid metabolization, it has not been used as an effective drug so far. To solve the problem of bioavailability of curcumin, gold nanoparticles (cAuNps) reduced and stabilized with curcumin have been prepared. Afterwards, study for their antioxidant defenses and its effect on oxidative stress has been implemented. Cell cytotoxicity of both cAuNps (2.91677×102 – 2.91677×1012 particles ml-1) and free curcumin (1mM-128mM) were studied by 3-(4, 5-dimethylazol-2-yl)-2, 5-diphenyl-tetrazolium bromide) (MTT) assay. From the above studies, it was found that cAuNps could ameliorate the antioxidants defenses and could quench the ROS and RNS generated in the cells more significantly compared to free curcumin. This phenomenon is due to the abstraction of H atoms from phenolic functional groups of curcumin in the nanoconjugate form. Thus, the study proposes a strategy for increasing the bioavailability of curcumin as a therapeutic agent as well as increasing its activity due to the synergistic effect of gold conjugated to it.
Keywords: Antioxidant, curcumin, oxidative stress, reactive oxygen species, reactive nitrogen species.